Prevalence and risk factors for Sick Building Syndrome among Italian correctional officers: A pilot study - Francesco Chirico; Giuseppe Ferrari; Giuseppe Taino; Enrico Oddone; Ines Giorgi; Marcello Imbriani (Journal of Health and Social Sciences)
Introduction: Over the past two decades, numerous studies on indoor air and the Sick Building Syndrome (SBS) have been conducted, mostly in office environments. However, there is little knowledge about SBS in police officers. This study was aimed to fill this gap. Methods: A cross-sectional questionnaire survey was conducted in 2016 at the Triveneto Penitentiary Center, Northern Italy. Chi-square was used to test the difference of prevalence between office workers (OWs) and correctional officers (COs) of personal characteristics, cases of SBS, and general and mucocutaneous symptoms associated with SBS. A binary logistic regression was used to identify among individual, environmental, and psychosocial characteristics, factors associated with correctional officers’ Sick Building Syndrome. Results: Chi-squared analyses revealed that there were statistically significant differences in the estimated prevalence of SBS general symptoms (χ2 (1) = 12.22, P < .05), SBS mucocutaneous symptoms (χ2 (1) = 9.04, P < .05), and cases of SBS (χ2 (1) = 4.39, P <.05) between COs and OWs. COs reported that their health had been affected by the passive smoking (β = 2.34, P < .05) and unpleasant odour (β = 2.51, P < .05) as environmental risk factors; work-family conflict (β = 2.14, P < .05), psychological and physical isolation (β = 2.07, P < .05), and negative public image (β = 2.06, P < .05) as psychosocial risk factors. Finally, atopy (β = 2.02, P < .05) and to be current smoker (β = 2.02, P < .05) were statistically significant behavioral predictors of SBS among correctional officers. Discussion: Our survey showed that symptoms compatible with the sick building syndrome are common in correctional officers and that psychosocial work climate and exposure to passive smoking could have a strong influence on the prevalence of both general and mucocutaneous symptoms associated with SBS. A health policy for passive tobacco smoking within prisons, and for work-related stress management among COs could improve occupational wellness and decrease potential SBS symptoms among COs.